Feasibility and effectiveness of two built environmental interventions on physical activity among 3–5‐year‐old preschoolers. Issue 3 (8th July 2019) - Robinson, Jennifer C.; Temple, Melissa L.; Duck, Angela; Klamm, Melissa
Abstract: Purpose: The purpose was to examine the feasibility and preliminary effectiveness of two built environmental interventions with Head Start preschool children to increase minutes and intensity and total physical activity (PA). Design and Methods: A prospective, quasi‐experimental, repeated measures design was conducted in two Head Start centers. Centers were randomly assigned to one of two intervention arms. Intervention Arm I added portable play equipment to the school environment; Arm II introduced portable play equipment plus PA education for staff and children. PA was measured during school using accelerometers and by observation using SOPLAY. The data were analyzed using repeated measures ANOVA. Results: Ninety‐seven children and eight staff were enrolled; valid PA data were available for 56 children (58%). Minutes of PA were highest at baseline in both groups and declined over the intervention. PA in Arm I decreased 22 min from weeks one to three and 12 min ( p  < .001) from weeks 3 to 6. In Arm II, PA declined 33 min from weeks one to three and 20 min ( p  < .001) from weeks 3 to 6. Practice Implications: Nurses work to maintain and improve health at multiple levels of influence and are in strategic positions to educate and support PA to maintain and improve the health of all ages. School‐based PA interventions have been reported with varying success. The feasibility of this study provides insight into the challenges in planning and conducting school‐based interventions including enrollment, attrition, and accelerometer wear‐time compliance. Despite our interventions, there was no positive response to either intervention, with PA declining at each time period in both groups. However, baseline PA was significantly higher than in previous studies. Schools can provide children with opportunities to accumulate PA.